Pitch Patterns in Vocal Expression of ’Happiness’ and ’Sadness’ in the Reading Aloud of Prose on the Basis of Selected Audiobooks - Stolarski, Łukasz (Research in Language, 2015)
The primary focus of this paper is to examine the way the emotional categories of “happiness” and “sadness” are expressed vocally in the reading aloud of prose. In particular, the two semantic categories were analysed in terms of the pitch level and the pitch variability on a corpus based on 28 works written by Charles Dickens. passages with the intended emotional colouring were selected and the fragments found in the corresponding audiobooks. They were then analysed acoustically in terms of the mean F0 and the standard deviation of F0. The results for individual emotional passages were compared with a particular reader’s mean pitch and standard deviation of pitch. The differences obtained in this way supported the initial assumptions that the pitch level and its standard deviation would raise in “happy” extracts but lower in “sad” ones. Nevertheless, not all of these tendencies could be statistically validated and additional examples taken from a selection of random novels by other nineteenth century writers were added. The statistical analysis of the larger samples confirmed the assumed tendencies but also indicated that the two semantic domains may utilise the acoustic parameters under discussion to varying degrees. While “happiness” tends to be signalled primarily by raising F0, “sadness” is communicated mostly by lowering the variability of F0. Changes in the variability of F0 seem to be of less importance in the former case, and shifts in the F0 level less significant in the latter.